2020
DOI: 10.1007/s40618-020-01438-8
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation during the SARS-CoV-2 pandemic

Abstract: Purpose Sperm cryopreservation is fundamental in the management of patients undergoing gonadotoxic treatments. Concerns have risen in relation to SARS-CoV-2 and its potential for testicular involvement, since SARS-CoV-2-positive cryopreserved samples may have unknown effects on fertilization and embryo safety. This study therefore aimed to analyze the safety of sperm cryopreservation for cancer patients after the onset of the pandemic in Italy, through assessment of the risk of SARS-CoV-2 exposure and viral RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
0
15
0
6
Order By: Relevance
“…Moreover, the authors were not able to detect COVID-19 RNA in testicular tissue from deceased subjects [ 113 ]. A case report showed that a 31-year-old man recovering a mild form of COVID-19 had no detectable virus in his ejaculate within fifteen days from the onset of the disease [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the authors were not able to detect COVID-19 RNA in testicular tissue from deceased subjects [ 113 ]. A case report showed that a 31-year-old man recovering a mild form of COVID-19 had no detectable virus in his ejaculate within fifteen days from the onset of the disease [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sperm banking should be offered; however, preliminary assessment and molecular confirmation of the absence of COVID-19 in seminal fluid in asymptomatic men should be performed, as viruses stored in liquid nitrogen have been shown to retain their pathogenic properties [ 27 28 ]. Prior studies have shown this preliminary evaluation to aid in the safety of sperm cryopreservation [ 29 ]. Still, larger cohorts of current or previously COVID-19 infected men are needed to confirm the safety of cryopreservation and assisted reproduction techniques in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Bwire et al reported a low (1.0%) detection of SARS-CoV-2 in blood samples [6]. It could be that the virus only spreads to blood under certain circumstances, such as the acute phase or severe disease, and then to other organs such as the testis [39].…”
Section: Discussionmentioning
confidence: 99%